China and Latin America: Belt and Road Initiative and the potential of the Bioceanic corridors for the region - Haro-Sly, Maria José (2019)
In 2013, Chinese President Xi Jinping launched the Belt and Road Initiative (BRI), an infrastructure building and international investment plan aiming to increase connectivity and development opportunities among emerging countries. The present paper intends to analyze the potential of the BRI for Latin America, presenting the case studies of bioceanic projects: Capricornio Corridor (Argentina and Chile); and Central Corridor (Brazil, Bolivia and Peru). The success of these projects will depend upon the national consensus reached in the different countries concerning their development path, the regional coordination to present unified position with a coherent strategy towards articulating relations with China. The major challenge is how LA countries are able to secure necessary infrastructure projects and avoid the risks concerning economic re-primarization.